Kinerja Aspek Sosial dalam Pengelolaan Hutan Alam Lestari: Studi Kasus pada HPH PT. Sumalindo Lestari Jaya (SLJ) II Provinsi Kalimantan Timur - Muljono, Pudji (Sodality: Jurnal Sosiologi Pedesaan, 2009)
Social aspect is one of important aspects to be considered in the analysis of sustainable forest management performance. This article discusses the analysis of social aspect of sustainable forest management as taking place at one of production unit of PT (SLJ) II in East Kalimantan. Ten indicators were employed to help elaborate sustainable forest management performance in this study. These indicators were considered to represent keys social aspect influencing the management performance at that unit of production. The employed indicators are to comply with sustainable forest management certification system as formulated by Lembaga Ekolabel Indonesia 2000. Based on the analysis, it is indicated that PT SLJ II accomplished good enough social performance in running sustainable forest management. However, it is also shown that the implementation of good social aspect performance did not help the company to improve the level of community welfare status yet. The finding of the study is expected to give an enrichment matter to the process of how sustainable forest management should be operated and be achieved in the field. Keywords: social aspect performance, sustainable forest management